Factors Influencing Healthcare Providers and Barriers in Conducting Sexual Health Care Discussions with Cancer Patients: A Systematic Review - Septyani Windi Utami; Yati Afiyanti; Wiwit Kurniawati; Imami Nur Rachmawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Sexuality is often overlooked in the context of cancer treatment for women. Healthcare providers in providing holistic care for cancer patients have not focused on the aspect of sexuality. Objective to identify the various factors that influence healthcare providers to discuss sexual care and the barriers they face when addressing sexuality in cancer patients. A systematic review using databases such as Science Direct, Proquest, Wiley, Springer with a time range of 2019-2024 in English, resulting in 10 articles. Factors influencing healthcare providers in discussing sexual care include internal factors such as knowledge, attitude, self-efficacy, age, years of work, and competency, as well as external factors such as the work environment and cultural norms. Barriers include limited service time, lack of training, and insufficient institutional support.